2015
DOI: 10.1007/s10198-015-0756-z
|View full text |Cite
|
Sign up to set email alerts
|

An empirical comparison of Markov cohort modeling and discrete event simulation in a capacity-constrained health care setting

Abstract: The MM and DES-no-DQ ICER estimates differed due to the MM having implicit delays built into its structure as a result of having fixed cycle lengths, which are not a feature of DES. The non-DQ models assume that queues are at a steady state. Conversely, queues in the DES-DQ develop flexibly with supply and demand for resources, in this case, leading to different estimates of resource use and CE. The choice of MM or DES (with or without DQ) would not alter the reimbursement of OPSC as it was highly cost-effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…RM performed at an aggregate level). Out of the 10 articles, 5 studies applied RM at an organisational level [19][20][21][22][23]] and 5 at a national level [24,[26][27][28][29].…”
Section: Searches and Siftingmentioning
confidence: 99%
See 4 more Smart Citations
“…RM performed at an aggregate level). Out of the 10 articles, 5 studies applied RM at an organisational level [19][20][21][22][23]] and 5 at a national level [24,[26][27][28][29].…”
Section: Searches and Siftingmentioning
confidence: 99%
“…The outcomes that were observed in these studies included total flow time [19,20,[27][28][29], waiting time [19][20][21][22][23][24][26][27][28][29], waiting probability [28], patient throughput [19-21, 23, 27, 28], resource utilisation [19-21, 23, 26, 28], queue length [21,23,24,28,29], probability of abandonment [28], and service level [28]. In one study observed [22], only one RM outcome was mentioned (waiting time); the remainder of these studies reported multiple outcomes.…”
Section: Searches and Siftingmentioning
confidence: 99%
See 3 more Smart Citations